Physiotherapy for respiratory diseases - Gałuszka, Aleksandra (Journal of Education, Health and Sport, 2022)
The respiratory system is crucial to human life. Its performance determines the quality of life. Physical training helps patients suffering from various diseases of this system to build up physical fitness, improve breathing mechanics and reduce clumsy secretion in the bronchial tree. The right choice of techniques for working with such a patient is important. They use fitness training, strength training, breathing exercises, bronchial tree cleansing. Always consider possible contraindications